1978
DOI: 10.1172/jci108998
|View full text |Cite
|
Sign up to set email alerts
|

Cardiac and Renal Prostaglandin I2

Abstract: A B S T R A C T Both the isolated perfused rabbit heart and kidney are capable of synthesizing prostaglandin (PG) I2. The evidence that supports this finding includes: (a) radiochemical identification of the stable end-product of PGI2, 6-keto-PGF,l, in the venous effluent after arachidonic acid administration; (b) biological identification of the labile product in the venous effluents which causes relaxation of the bovine coronary artery assay tissue and inhibition of platelet aggregation; and (c) confirmation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

1979
1979
1985
1985

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 168 publications
(25 citation statements)
references
References 32 publications
0
25
0
Order By: Relevance
“…Vessel injury is normally associated with transient vasoconstriction which is followed by vessel relaxation. We suggest that the vessel relaxation after constriction is contributed to by smooth muscle-relaxing prostaglandins that are released from the vessel wall in response to injury (27)(28)(29), and that the inhibition of the synthesis of these prostaglandins leads to a sustained vasoconstriction. This vasoconstriction has a hemostatic effect when the vessel wall in either normal or thrombocytopenic animals is damaged, or the vessels in the microcirculation transected.…”
Section: Resultsmentioning
confidence: 92%
“…Vessel injury is normally associated with transient vasoconstriction which is followed by vessel relaxation. We suggest that the vessel relaxation after constriction is contributed to by smooth muscle-relaxing prostaglandins that are released from the vessel wall in response to injury (27)(28)(29), and that the inhibition of the synthesis of these prostaglandins leads to a sustained vasoconstriction. This vasoconstriction has a hemostatic effect when the vessel wall in either normal or thrombocytopenic animals is damaged, or the vessels in the microcirculation transected.…”
Section: Resultsmentioning
confidence: 92%
“…DISCUSSION The involvement of phospholipases A2 in prostaglandin biosynthesis by intact cells has been suggested for many years. Free fatty acid levels are very low in most tissues, and phospholipase activation is believed to be required for prostaglandin biosyn- thesis (1,5,16,(19)(20)(21)(22). This activation can be brought about in different tissues through a variety of stimuli, such as bradykinin, angiotensin II, vasopressin, thrombin, collagen, serum, ionophore A23187, and trypsin (2)(3)(4)(5)(6)(7)(8)(9)(10)(11)(12)(19)(20)(21)(22).…”
Section: Methodsmentioning
confidence: 99%
“…Undisturbed endothelial cell monolayers can also readily transform PGH2 to prostacyclin (Marcus, Weksler & Jaffe, 1978). However, the hypothesis was challenged by Needleman and associates (Needleman, Bronson, Wyche, Sivakoff & Nicolaou, 1978) who demonstrated that, while arachidonic acid was rapidly converted to prostacyclin by perfused rabbit hearts and kidneys, PGH2 was not readily transformed. They concluded that some degree of vascular damage was necessary for the endoperoxide to be utilized by prostacyclin synthetase.…”
Section: Generation By the Vessel Wallmentioning
confidence: 99%